Path dependence in policies supporting smart specialisation strategies: Insights from the Basque case - M. Valdaliso, Jesús; Magro, Edurne; Navarro, Mikel; Jose Aranguren, Mari; R. Wilson, James (European journal of innovation management, 2014)
Purpose - The purpose of this paper is to apply the path dependence theoretical framework to STI policies that support research and innovation strategies for smart specialisation (RIS3). Design/methodology/approach - Review of the recent literature on the phases, sources of reinforcement and change mechanisms (layering, conversion, recombination, etc.) present in path-dependent processes, as well as the role played by mental frameworks, political agents and power relations; and its illustration and testing over 30 years of STI policy development in the Basque Country. Findings - How to operationalise the analysis of continuity and change of STI policies supporting RIS3 policies characterised by path dependence processes. Likewise, learnings from the analysis of Basque case regarding the types of challenges that European regions will face as they design their RIS3, according to their degree of maturity in STI policies. Originality/value - It is the first time that the recently developed tools for analysis of path-dependent processes are applied to the development of STI policies supporting RIS3 policies.